The Proof Is in the Adminicula: The Judicial Work of Evaluating the Proofs - Lagges, Patrick (The jurist, 2024)
The Code of Canon Law lists six sources of proofs in contentious trials (cc. 1526-1586): the declaration of the parties, documents, witnesses and testimonies, experts, judicial examination and inspection, and presumptions. But there are also four other sources of proof contained in the law: indicia, adminicula, circumstances of persons and things, and the knowledge and conscience of the judge. This article examines the above-mentioned sources of proof and indicate how the judge might be assisted by the four latter sources. Indicia look forward and assist the judge in areas which need further exploration. Adminicula look at what has already been presented in order to confirm certain points of the case. The circumstances of things and persons allows the judge to take a more wholistic view of the matter. The knowledge and conscience of the judge ensures that a decision will have moral integrity, be fair, impartial, and just. The article concludes with a description of the dialog that must take place between the judge and the various proofs that are presented, particularly with regard to issues related to memory, to the examination of documents, and to the evaluation of expert testimony.